O uso das tecnologias de informação e comunicação (TIC) no contexto da aprendizagem significativa para o ensino de ciências - Padilha, Andrea da Silva Castagini (2014)
This thesis had investigated the main obstacles that science teachers have when using Information and Communication Technologies (ICT), especially Internet, as a teaching resource. This was composed as a qualitative research and has as the main objective to develop a guide with methodological suggestions for using virtual digital resources, in order to assist in the difficulties identified altogether with Science teachers of the investigated school. For subsidize the guide for the use of ICT in Science teaching, we chose as theoretical basis from Meaningful Learning and TPACK model (Technological Pedagogical Content Knowledge). The group of Science teachers of a public school was investigated. The research instrument was an interview script; it was developed and validated beforehand, it had questions about what teachers would know about the use of technologies in the context of teaching their subjects, their difficulties, anxieties, impressions and methodologies used in the presence of ICT. The content of the interviews were transcribed and examined from the perspective of Content Analysis and related with assumptions of Meaningful Learning and the literature on the use of ICT in educational context. The results obtained have shown that the difficulties still are with integrating digital technologies (in particular, the use of Internet) with Science teaching in Public School. The lack of infrastructure and support for the use of technologies are obstacles presented by the teachers. Another problem they have mentioned was the lack of Service-learning in Teacher Education for a meaningful use of ICT in the context of learning Science. At the same time, the group interviewed made use of Internet to prepare their classes, making researches for current themes and organize educational planning. The teachers said they did not use Internet at school with students and justified this choice due to the [lack of] conditions presented in the establishment. From these data and the literature reviewed, a guide of methodological suggestions for the use of ICT in Science classes was created and it is also the product of this Master’s thesis. This can be a potentially significant material for the Continuing Education for these teachers in this area. It was concluded that technological literacy of Science teachers had progressed, but there is still a long way to go in order to acquire full appropriation of technologies as resources in a Meaningful Learning.